Erratum to “The usefulness of surgical drains on short term outcomes among patients undergoing craniotomy at the Bugando Medical Centre, Mwanza Tanzania” [World Neurosurgery: X(22C) (2024) (100323)] - Dennis Onsombi; Gerald Mayaya; Vladimir Herrera; Anton Manyanga; Washington Leonald; Samuel Byabato; James Lubuulwa (World Neurosurgery: X)
Background: Postcraniotomy surgical drain placement is commonly used worldwide after various cranial surgical interventions despite the controversy surrounding their use leaving it to the surgeon's preference rather than evidence based practice. However, with the paucity of published data regarding utility in Tanzania, we sought out to determine the occurrence of SFC, incidence of SSI and the length of hospital stay among patients who underwent craniotomies. Methods: This was a prospective cohort study conducted to determine the occurrence of SFC, rate of SSI and the length of hospital stay among patients who underwent craniotomies at BMC from Feb to June 2022. Patients were divided into two groups based on whether or not have undergone placement of drainage tube following craniotomy and data was collected, entered into Epi-Info version 7.0, extracted as Microsoft-Excel and analyzed using STATA v.13.0 software. Medians and proportions were utilized to describe data, and appropriate statistical tests applied whenever necessary to check for statistical significance. Ethical clearance was sought from the institution board to proceed with the study. Results: A total of 77 patients were enrolled into the study, the median patient age (IOR) was 33(18–55) years, and 55 % of patients were males, giving male to female ratio of 2:1. Postcraniotomy drains were used in 36.36 %(28/77) of the patients. Of the craniotomy procedures 52(67.5 %) were due to trauma. Surgical site infection was encountered in 4 patients (5.2 %), subgaleal fluid collection among 11 patients (14.28 %) although this was not significant among the two groups on univariate analysis p = 0.538 and 0.624 respectively. The length of hospital stay was similar in both drainage and non-drainage groups (p = 0.498). In a bivariate analysis on drain use vs patient factors, dural closure (P value= <0.001),skin closure (P value= <0.001) and cormobidities (p value = 0.013),for which on further multivariate regression, watertight dural closure (p = 0.015, OR = 14.15) was found to be associated with less likelihood of drainage use. Conclusion: In this single center observational study, we noted that outcomes of patients with post-craniotomy drains were largely equivalent and non-inferior to those without drains who underwent craniotomy for similar neurosurgical conditions at our institution with no statistical significance in terms of occurrence of subgaleal fluid collection, incidence of surgical site infection and length of hospital stay. The use of watertight dura closure significantly reduces the occurrence of SFC. Larger well randomized control and multicentered studies are recommended to further validate our findings.